PENGARUH MODEL GROUP INVESTIGATION (GI) BERBASIS CASE METHOD TERHADAP KETERAMPILAN KOLABORASI DAN PEMECAHAN MASALAH - Herlinda Oktavi Nayla; Ririn Andriani Kumala Dewi; Kiki Fatkhiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study originated from the recognition that students lacked sufficient exposure to collaborative learning environments and had limited experience in structured problem-solving. The research set out to analyze the impact of implementing the Group Investigation model, combined with the Case Method approach, on enhancing students’ teamwork and problem-resolution capabilities. A true experimental method was applied, utilizing a pretest-posttest control group design, and the research was conducted at MI Miftahul Ulum 2 Kaplongan Lor. The participants included 40 students, evenly assigned to experimental and control groups. Data collection instruments included essay-based assessments to gauge problem-solving and closed-format questionnaires to measure collaboration. Analysis through independent samples t-tests revealed meaningful distinctions between the two groups in both areas, as indicated by an Asymp. Sig. (2-tailed) value of 0.000. The R² value of 0.462 suggests that 46.2 percent of the variance in problem-solving improvement could be linked to the intervention. These results demonstrate that the Group Investigation learning strategy, when integrated with the Case Method, is effective in significantly strengthening both collaborative and problem-solving skills among students.